PENGARUH PEMBELAJARAN MENGGUNAKAN TABLET BERBASIS QR-CODE UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SDN 1 REJOSO - Binti Aisah; Ulhaq Zuhdi (STKIP Subang, 2023)
Learning is very meaningful for students, learning requires learning media, learning resources and appropriate learning methods to be applied by teachers to achieve learning objectives. This research is a Classroom Action Research (PTK). This class action research was conducted in class IV of SDN 1 Rejoso which aims to see the effect of using tablet for learning media on students' learning interest. Based on the data in table 1 above, it can be concluded that the data from the pretest control class has a minimum pretest value of 48, a maximum pretest value of 81, a mean value of 62.89 and a standard deviation value of 9.8. Based on the table. 2 above it can be concluded that the data from the control class pretest has a minimum pretest value of 48, a maximum pretest value of 81, a mean value of 65.89 and a standard deviation value of 9.1. Based on the MANOVA test, a significance value of 0.5 was obtained. If the sign value is less than 0.5 then Ho is rejected, then Ha is accepted which shows the influence of the learning media used. Based on the research conducted, there is a good effect on the results of the application of video learning media, quizzes, games and reflection by scanning barcodes. Good student enthusiasm will give good results, if students are enthusiastic about participating in learning then they will understand what is being learned can also provide motivation and interest in learning so that student learning outcomes can increase